Mental Hospitals in India in the 21st century: transformation and relevance. (20th December 2016) - Murthy, P.; Isaac, M.; Dabholkar, H.
Abstract : Mental hospitals in India, as elsewhere in the world, have played an important role in the care of persons with mental illness. Since their inception, they have both been decried for gross violations of human rights and dignity as well as lauded as places of refuge and care for persons turned away by the communities. In a country where community interventions for mental health care are still fragmentary, the mental hospital still continues to be a relevant and legitimate locus of care along with other limited resources available for the care of persons with mental illness outside of the family. In India, positive changes in the infrastructure and resourcing of mental hospitals, reductions in involuntary admissions and improvements in facilities have largely occurred through judicial interventions. Recent pilot interventions for rehabilitation of long-stay patients point towards the need to develop rehabilitation and community facilities for persons with severe mental illness.